1999
DOI: 10.1211/0022357991773401
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Oren-gedoku-to on Experimental Colitis in Rats

Abstract: In Japan and China, Oren-gedoku-to (a complex mixture of ingredients derived from plants) has been used as a herbal medicine in the treatment of inflammatory and ulcerative diseases. In other countries salicylazosulfapyridine has been used to treat inflammatory bowel disease. In this study, we have compared the effect of Oren-gedoku-to with salicylazosulfapyridine on trinitrobenzene-sulphonic acid-induced colonic damage in rats, a model representative of ulcerative colitis and Crohn's disease in man. Oren-gedo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 38 publications
1
14
0
Order By: Relevance
“…Thus, "heat removal" with an herbal medicine may not be directly related to blood flow changes. It has been reported that Orengedokuto reduces the levels of prostaglandin E2, interleukin-8, and leukotriene B4 in inflammatory bowel disease (Zhou and Mineshita 1999;Miura et al 2007). Thus, "heat removal" with Orengedokuto in traditional medicine may be related to a reduction in the levels of such inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, "heat removal" with an herbal medicine may not be directly related to blood flow changes. It has been reported that Orengedokuto reduces the levels of prostaglandin E2, interleukin-8, and leukotriene B4 in inflammatory bowel disease (Zhou and Mineshita 1999;Miura et al 2007). Thus, "heat removal" with Orengedokuto in traditional medicine may be related to a reduction in the levels of such inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, suppression of PGE2 production by OGT has also been reported in the TNBS-induced colitis model. 19) These findings had initially led to the assumption that OGT may have NSAID-like properties. However, in the present study we found that OGT pretreatment does not exacerbate NSAID-induced enteropathy but effectively inhibits NSAIDinduced severe intestinal injury (Figs.…”
Section: Fig 10 Localization Of Cox-2 Expressing Cellsmentioning
confidence: 99%
“…OGT decreases intestinal injury in dextran sulfate sodium (DSS)-and trinitrobenzene sulphonic acid (TNBS)-induced animal models of enteropathy. [17][18][19] In the present study, we describe the effect of OGT on lethality, intestinal injury, and PGE2 depletion induced by subcutaneous indomethacin injection, and we discuss OGT's possible therapeutic value for the treatment of IBD and adverse reactions to NSAIDs.…”
mentioning
confidence: 99%
“…The therapeutic effects of HLJDT have been studied in a variety of rat disease mod- els such as the ischaemia/reperfusion-induced brain injury (Hwang et al, 2002), stress-induced gastric mucosal lesions (Ohta et al, 1999a,b), trinitrobenzene-sulphuric acid-induced colonic damage (Zhou and Mineshita, 1999) and carbon tetrachloride-induced liver injury (Ohta et al, 1997). All these studies have demonstrated the common beneficial effect of HLJDT on reducing leukocyte infiltration and associated tissue injury.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo animal or in vitro studies on the anti-inflammatory effects of HLJDT have been carried out in a great variety of acute and chronic inflammatory diseases, either pathogenic microbesrelated or not. Based upon research results from Medline databases, these could be divided into four categories as (1) infection diseases: gastroenteritis, in vitro antimicrobial activity (Franzblau and Cross, 1986), intestinal parasite infection (Yang et al, 1996), acne (Higaki et al, 1996), gastric ulcer (Takase et al, 1989;Ohta et al, 1999a,b); (2) autoimmune or allergic diseases: inflammatory bowel diseases (Zhou and Mineshita, 1999), atopic dermatitis (Nose et al, 1999); (3) chemicals or trauma-induced diseases: hepatoxininduced hepatitis (Lin et al, 1996;Ohta et al, 1997Ohta et al, , 1998Ohta et al, , 2004, post-traumatic inflammatory aqueous flare elevation after smallincision cataract surgery (Ikeda et al, 2001;Nagaki et al, 2001), mucositis caused by anticancer drugs (Yuki et al, 2003) and (4) others: ischaemia/reperfusion injury-associated inflammatory process (Kabuto et al, 1997;Kondo et al, 2000;Xu et al, 2000;Hwang et al, 2002), and atherosclerosis. These studies experimentally demonstrated HLJDT as an effective anti-inflammatory agent.…”
Section: Introductionmentioning
confidence: 99%